Effect of milk as a mouthwash on dentin hypersensitivity after non-surgical periodontal treatment - Ashkan Salari; Fereshteh Naser Alavi; Komeil Aliaghazadeh; Masumeh Nikkhah (Journal of Advanced Periodontology and Implant Dentistry)
Background. Limited evidence is available on the effect of milk as a mouthwash on treating dentin hypersensitivity. The present study aimed to compare the effect of milk as a mouthwash with one anti-hypersensitivity mouthwash in decreasing dentin hypersensitivity after non-surgical periodontal treatment. Methods. Patients with generalized moderate-to-severe chronic periodontitis were selected randomly in the present study and underwent scaling and root planing (SRP). Seventy patients with severe dentin hypersensitivity after two days were assigned to two groups. In group A, the patients were asked to use milk as a mouthwash, and in group B, the patients were asked to use anti-hypersensitivity Misswake mouthwash. The patients’ hypersensitivity was measured during follow-up visits. The independent t-test was used to compare denim hypersensitivity between the two groups. Statistical significance was set at P<0.05. Results. The results showed a significant decrease in dentin hypersensitivity in both groups on days 15 and 30. In the milk group, 11 and 29 patients fully recovered from dentin hypersensitivity on days 15 and 30, respectively. However, in the anti-hypersensitivity mouthwash group, 8 and 27 patients fully recovered from dentin hypersensitivity on days 15 and 30, respectively. Therefore, more patients benefited from the anti-hypersensitivity effects of milk as a mouthwash. However, the differences were not significant during the whole treatment sessions. Conclusion. Using milk as an inexpensive and available mouthwash can decrease dentin hypersensitivity after SRP.